2001
DOI: 10.1046/j.1365-2389.2001.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the phosphorus sorption capacity of acidic soils in Ireland

Abstract: Summary The test for the degree of phosphorus (P) saturation (DPS) of soils is used in northwest Europe to estimate the potential of P loss from soil to water. It expresses the historic sorption of P by soil as a percentage of the soil's P sorption capacity (PSC), which is taken to be α (Alox + Feox), where Alox and Feox are the amounts of aluminium and iron extracted by a single extraction of oxalate. All quantities are measured as mmol kg soil−1, and a value of 0.5 is commonly used for the scaling factor α i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 30 publications
10
89
6
Order By: Relevance
“…The P sorption increased rapidly with time until about 48 h reaction time and continued for a longer time, even though the sorption rates became slower. This sorption behaviour is typical and is well reported in the literature [26,34,88].…”
Section: Soil P Sorption Kineticssupporting
confidence: 84%
See 2 more Smart Citations
“…The P sorption increased rapidly with time until about 48 h reaction time and continued for a longer time, even though the sorption rates became slower. This sorption behaviour is typical and is well reported in the literature [26,34,88].…”
Section: Soil P Sorption Kineticssupporting
confidence: 84%
“…where the saturation factor has been estimated in various studies with the value of 0.5 [33,34,40,54,55]. Van der Zee [56] reported values in the range of 0.4 to 0.6 (average of 0.5).…”
Section: Soil (De)sorption Kinetics Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…At a laboratory scale, increasing soil P in noncalcareous soils increases water soluble P but only markedly when the degree of P saturation of soils exceeds 25% (Maguire et al 2001). This nonlinear response therefore can explain why catchment P exports did not increase until after 1960, whereas soil P had been increasing since at least 1925 and probably since 1870 (Foy et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Leinweber et al (1999) found that total P concentrations in lysimeters under 20 field sites in Germany were correlated with the DSPS, measured as the ratio of acid ammonium oxalate-extractable P to oxalate-extractable Al and Fe. Other researchers have shown that the potential for P leaching increases greatly when the DSPS, based on oxalate-extractable P, Al and Fe, exceeds 25% (Maguire et al 2001;McDowell and Sharpley 2001b). In Quebec, the DSPS method based on the ratio of Mehlich-3 extractable P to Mehlich-3 extractable Al has been adopted for acid soils with less than 6 g kg -1 of oxalate-extractable Al (Beauchemin and Simard 1999;Khiari et al 2000).…”
mentioning
confidence: 99%